Finite element method for the static and dynamic analysis of FRP guyed tower. Issue 3 (27th August 2018) - Alshurafa, Sami; Alhayek, Hanan; Polyzois, Dimos
Graphical abstract: Abstract: A research study has been carried out to provide design guidelines for glass-fiber reinforced polymer (GFRP) guyed tower. Both material testing and theoretical analysis are involved. The tower examined in this study has 81 m in height with a uniform equilateral triangle cross section having sides of 450 mm. The tower supported by seven sets of guy wires oriented at 120°, each set consisting of three guy wires. The tower was assumed to be supported at the base by means of a pinned connection to provide full moment release. The tower was analyzed using the finite element ANSYS software and was designed to satisfy both the ultimate and the serviceability limit state requirements of the CSA-S37-01 Standard. The guyed tower was analyzed in static to evaluate the tower strength failure using several advanced failure theories. Modal analysis and full dynamic analysis using CSA-37-01 Standard were extensively performed to evaluate the vibration performance and to obtain an accurate dynamic response of the full-scale tower. The paper presents the results obtained from material testing and from a finite element, ANSYS models developed for the static and dynamic analysis of the multi-cells 81 m lightweight-guyed towers.